The Influence of Social Media Influencer Marketing, Self-Regulation, and Viral Marketing on Purchase Intention on Tokopedia - Dimas Haydar Farras; Tias Andarini Indarwati (International Journal of Social, Economic, and Business, 2025)
The increasing competitiveness of e-commerce marketplaces in Indonesia underscores the importance of effective marketing strategies to enhance purchase intention among Generation Z consumers. This study aims to identify the influence of social media influencer marketing, self-regulation, and viral marketing on purchase intention. The population in this study consists of individuals aged 13–28 years (Generation Z), residing throughout Indonesia, who have never made a purchase on Tokopedia after seeing an advertisement from a Tokopedia social media influencer. The sampling technique used in this study is purposive sampling, with a total of 155 respondents. This study employs multiple linear regression analysis, which shows that social media influencer marketing does not affect purchase intention, while self-regulation and viral marketing both have an influence on purchase intention. The practical implications of this study suggest that Tokopedia should reconsider the effectiveness of its social media influencer marketing strategies, develop features that help consumers become more aware of their shopping decisions, and pay attention to the content of viral messages, such as message uniqueness, emotional impact, and creativity.